Electronic Spectral Characterization of Pr(III) Systems Involving Sulphonanilide Environment in DMF Medium - Pandey, H.K.; Joshi, G.K.; Shrimali, S.S. (Asian Journal of Chemistry, 2010)
Electronic spectral parameters, viz., nephelauxetic ratio (β), bonding parameter (b½) and Judd-Ofelt intensity parameter (Tλ) have been computed for some modified doped systems involving Pr(III) surrounded by sulphonanilide ligand. Oscillator strength of all the four bands (3P2, 3P1, 3P0and 1D2 levels) in each system has been reported and recalculated using Judd-Ofelt equation. The r.m.s. deviations have been found to be ±1.82 X 10–9 to ±9.43 X 10–9. A linear correlation between oscillator strength of hypersensitive band (3P2 level) and vT6 has been observed.